2020
DOI: 10.1108/gs-04-2020-0042
|View full text |Cite
|
Sign up to set email alerts
|

The most livable city selection in Turkey with the grey relational analysis

Abstract: PurposeThis study has two main objectives: (1) to expand the application areas of grey system theory and (2) to select the most livable city in Turkey.Design/methodology/approachChoosing the most livable city is a complex problem that requires many criteria to be considered. It is important to select decision points according to which the criteria selection will be made and to what extent the criteria will affect the evaluation. For this purpose, a questionnaire was prepared to determine the criteria to be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…e GRA has been successfully implemented in many areas. For example, Kose et al [13] identified the most livable Turkish city through the GRA. With the help of a GRA model, Peng et al [14] enumerated the health resources that satisfy the public in China.…”
mentioning
confidence: 99%
“…e GRA has been successfully implemented in many areas. For example, Kose et al [13] identified the most livable Turkish city through the GRA. With the help of a GRA model, Peng et al [14] enumerated the health resources that satisfy the public in China.…”
mentioning
confidence: 99%
“…Ozdemir et al [14] integrated FAHP and GRA methodologies for personnel selection. Kose et al [15] used GRA for the most livable city selection in Turkey.…”
Section: Information Resources and Technology;mentioning
confidence: 99%
“…Other applications of grey theory are also used for different purposes. Kose et al [17] used grey relational analysis to rank Turkey's cities and find the most liveable city. GP, sometimes referred to as grey forecasting, is a methodology derived from grey systems.…”
Section: Literature Reviewmentioning
confidence: 99%